Insomnia and anxiety: exploring their hidden effect on natural killer cells among young female adults - Alhamawi, Renad M.; Halawani, Fatmah A.; Hakeem, Sima F.; Alslimi, Hadeel A.; Alhamawi, Ebraheim M.; Aljohani, Ahmed M.; Mohammed, Ibrahim N.; Zahid, Heba M.; Almutawif, Yahya A. (Frontiers in Immunology, 2025)
IntroductionGeneralized anxiety disorder (GAD) is one of the most prevalent mental conditions globally, and it is frequently associated with sleep disturbances such as insomnia. Recently, these mental health conditions have been increasing in prevalence among younger generations, particularly among young women. Therefore, this study aimed to explore the relationship between anxiety, insomnia, and immune function, with a specific focus on natural killer (NK) cells.MethodsA cross-sectional study was conducted recruiting young female students under 25 years of age. Self-reported GAD-7 and insomnia symptoms were assessed using validated, previously published questionnaires, while immune cell profiles were measured by complete blood count (CBC) and flow cytometry.ResultsThe results revealed that 75% of participants experienced GAD-7 symptoms at varying severity levels, and over 50% reported insomnia. Interestingly, students with symptoms of GAD-7 had a lower percentage and number of circulatory NK cells and their subpopulation—CD16+CD56dim and CD16+CD56high—compared to normal students. Moreover, among students who were suffering from insomnia, higher GAD-7 scores were negatively associated with the proportion of total peripheral NK cells.DiscussionThese findings suggest that anxiety and sleep disturbances may compromise immune function and contribute to immune dysregulation. Raising awareness of these physiological effects may help in the prevention of inflammation-related diseases and cancers in young female populations.